Estimation of Carbon Stock and Carbon dioxide Equivalent (CO2-e) Absorption of Needle Leaved Tree and Mixed Broadleaved Trees of Nilbarahi Community Forest of Madhyapurthimi, Bhaktapur - Karn, Lalbabu Lal; Pant, Dipesh Raj; Pradhan, Bijay Lal; Jha, Vijay Kumar (Amrit Research Journal, 2025)
The Nilbarahi Community Forest contains the needle leaved tree species Pinus roxburghii (Chir pine) and mixed broad leaved tree species such as Schima wallichii, Engelhardtia spicata, Eurya acuminate, Litsea monopetala and Alnus nepalensis. This community forest’s some part is naturally of mixed broad leaved trees and some part is planted trees of Pinus roxburghii (Chirpine). The SRS method was used to determine the carbon component of the forest to assess the amount of carbon stock and carbon dioxide equivalent (CO2-e) absorption of needle leaved tree and the mixed broadleaved tree of the community forest. The carbon stock of the forest was measured per hectare basis of the biomass contained by the trees. It is very essential to know the type of trees that can absorb much carbon component from the atmosphere through Photosynthesis and store it in their leaves, branches, stems, barks and in the roots. The much carbon retained by the trees would help to mitigate the climate change. The biomass of the trees was determined by the biomass regression model and then the carbon retained in them was obtained by converting the biomass stock of trees into carbon stock by using the IPCC default carbon fraction of 0.47. After then the CO2-e absorption was calculated by multiplying one ton of carbon value to 3.67 tons of carbon dioxide equivalent (CO2-e) which was expressed in metric tons. The total above ground tree biomass was found 188.70 ton/ha at site-3 of mixed broad leaved forest seemed to be the highest biomass followed by the planted forest of Pinus roxburghii (Chir pine) at site-1 which had the biomass of 147.78 ton/ha. The carbon content of above ground tree biomass of the study area was also found to be 88.69 ton/ha followed by 69.45 ton/ha at site-3 and site-1 respectively. The study showed that the needle leaved trees (Pinus roxburghii) had low carbon stock than the natural mixed broadleaved trees in the Nilbarahi Community Forest. The CO2-e was also found to be highest as 295.21MT in the mixed broad leaved trees than the needle leaved conifer trees of 231.18 MT at site-3 and site-1 respectively. The average carbon stock and average CO2e was found to 72.41 t/ha and 241.03 MT in the Nilbarahi Community Forest. The biomass, carbon (C) stock and carbon dioxide equivalent (CO2-e) in the forest ecosystems of Nilbarahi which have been managed and conserved well by the community forest user groups could play an important role in carbon cycle and serve as significant carbon sink to reduce the burning issue of global warming.